Circulating current suppression method of grid-connected inverters in parallel using serial communication - Jeon, Se Bong; Cho, Sung Joon; Lee, Kyo Beum (Transactions of the Korean Institute of Electrical Engineers, 2021)
This paper proposes a circulating current suppression method of grid-connected inverters in parallel inverters using serial communication. The grid-connected inverter for large scale photovoltaic generation system consists of multiple modules in parallel based in unit inverter module. The existing method to synchronize PWM signals between inverter modules was implemented by CAN communication with high interrupt priority. However, the high priority of CAN communication can cause deterioration in current control performance due to limited resource of controller. This paper introduces an improved synchronization method of PWM signals with low interrupt priority using time stamp function. The effectiveness of the proposed method is verified by experimental results with 250kW inverter system.
Keywords: CAN communications; Circulating current suppressions; Control performance; Grid connected inverters; Large-scale photovoltaic generation; Parallel inverter; Serial communications; Synchronization method; Circulating current; Grid-connected inverter; PWM synchronization; Serial communication